A study on the nature of criminal offences in prisoners with psychiatric disorders - Suryavanshi, Sunilkumar R.; Netto, Ivan S. (International Journal Of Community Medicine And Public Health, 2021)
Background: There are very few Indian studies related to the nature of criminal offences in individuals with psychiatric disorders. Methods: Sample consisted of 50 prisoners admitted to a Mental hospital. Their diagnostic categorization was done according to ICD-10 diagnostic research criteria and criminal offences using the Indian Penal code (IPC). The criminal offences and nature of psychiatric illness were divided into two broad groups as violent/non-violent criminal offence and schizophrenia/non-schizophrenia groups respectively. Results: 46 males and 4 female prisoners participated. Murder (IPC 302) was the most common crime among the prisoners. 88% (44) of them had a history of violent crimes and 12% (6) had non-violent crimes. The violent crimes were mainly murder (IPC 302), attempt to murder (IPC 307), and culpable homicide not amounting to murder (IPC 304) and voluntarily causing grievous hurt by dangerous weapons (IPC 323, 324, 325, 326). The non-violent crimes were destroying, damaging or defiling (IPC 295), kidnapping (IPC 363), theft (IPC 379) and sexual crimes (IPC 376). All females had committed murder while males had other crimes in addition to murder. Conclusions: Murder, attempt to murder, rape, kidnapping, grievous injury and theft were the crimes committed by the prisoners. Murder was the most common crime committed by both male and female prisoners. Most prisoners with violent crimes (murder) had a diagnosis of schizophrenia. This has implications for mental health services, training of mental health professional research and policy in forensic psychiatry in the Indian setting.